Tingkat Pengetahuan Dan Kesadaran Mahasiswa Klaster Non-Kesehatan Universitas Malahayati Bandar Lampung Terhadap Penggunaan Antibiotik - Nurhayati, Dwy; Samor, Vania Amanda; Nurkhalika, Rachmi (Peneliti.net, 2024)
Antibiotic are overused and protected can make individual more susceptible to disease, leading to more complicated treatment due to development of bacterial antibiotic rasistancy. Lack of students understanding of antibiotics can increase the incidence of antibiotic resistancy because students are a source of information for society. Relying on that, this study aim to determine level of knowledge and awareness towards antibiotics resistancy and their correlation to demographic status of non-health cluster students at Universitas Malahayati Bandar Lampung. The study was conducted cross-sectionally, with descriptive and analysis with SPSS. Based on the results health cluster students at the University of Malahayati Bandar Lampung had a good level of knowledge (62%) and awareness (74%) of the antibiotics use, even though they did not study health, science non-health students have a sofficient level of knowledge. The Chi-square analysis showed that there was no relationship (p≥0.05) between students' demographic characteristics (age, gender and faculty) and the level of knowledge and awareness.